Theater in a crowded fire : ritual and spirituality at Burning Man - Gilmore, Lee, 1969- (University of California Press, 2010)
Gilmore's study brings new voices and experiences to current debates about religion versus spirituality through her richly textured descriptions of the characters, events, and spaces that make up the seemingly strange but culturally significant Burning Man festival. Readers will discover that Burning Man is a wonderful illustration of the dialectic between self and community at the heart of much of American religion today. Gilmore persuades us that those who trivialize this event by seeing it as a huge party, miss the ways in which Burning Man provides an unusual snapshot of diverse form.